Evaluating nurses' knowledge and skills in the detection of child abuse in the Emergency Department - Keane, C.; Chapman, Rose (Elsevier, 2008)
This commentary paper highlights the issue of child abuse and the important role that nursing staff working in the Emergency Department (ED) can play in halting the cycle of abuse. Child abuse is a worldwide problem that is occurring with increasing frequency. In fact in Australia over the last 5 years the number of child protection referrals has more than doubled. As well as the immediate physical damage child abuse causes, it can also escalate to result in more serious injury and death. Furthermore, children who are abused in their early years of life are at increased risk of a range of adverse long-term developmental problems. Research has demonstrated that there is a significant lack of detection of suspected cases of child abuse in the ED. In fact the true incidence of children presenting to hospital EDs with abuse is difficult to determine, and many cases remain undetected. Nursing staff are perfectly positioned to detect the signs that a child may be at risk of abuse. However, in order to identify these signs it is essential that ED nurses have the knowledge and skills necessary to do so. Failure to consider the possibility of abuse will mean that the appropriate diagnosis is not made and the child is returned to an abusive environment. Therefore, this paper offers ED nurses recommendations for future directions in research and interventions to improve the detection of child abuse in Western Australia.